Developing an Innovation Management Model that is Suitable to the Indonesian MSME Context - Mufron, Ali; Alves, Livia; Lima, Rafaela (Journal of Loomingulisus ja Innovatsioon, 2024)
The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has highlighted the need for an innovation management model tailored to their unique characteristics. Despite their economic importance, Indonesian MSMEs face challenges in managing innovation due to limited resources, technological constraints, and lack of formal structures. This study aims to develop an innovation management model specifically designed to meet the needs and conditions of Indonesian MSMEs. The research adopts a mixed-methods approach, combining qualitative interviews with MSME owners and managers, and quantitative surveys to gather data on innovation practices and challenges. A conceptual framework is then developed based on the data collected, incorporating best practices in innovation management tailored to the Indonesian context. The findings reveal that a flexible, resource-conscious approach to innovation management is essential for MSMEs, with an emphasis on collaborative networks, low-cost innovation strategies, and adaptive leadership. The proposed model is designed to facilitate innovation by overcoming resource limitations and fostering a culture of continuous improvement. In conclusion, the research contributes to the development of a contextualized innovation management model for Indonesian MSMEs, offering a practical framework for enhancing their competitiveness in a dynamic market.